TOWARDS AN AGENT FRAMEWORK FOR GRID COMPUTING - Khan, Majid Ali; Vaithianathan, Shankar K.; Sivoncik, Kresimir; Boloni, Ladislau (International Journal of Computing, 2014)
This paper presents an agent oriented approach for grid computing. As opposed to existing approaches, agent technology promises a more flexible approach, easier installation and management of the grid framework, and better ability to autonomously recover from failures. The semantically rich, ontological description of the grid applications, services and resources opens the possibility for better monitoring and resource management, and better user interfaces - both for customers and service providers.